1999
DOI: 10.1191/096120399678847777
|View full text |Cite
|
Sign up to set email alerts
|

Immunological abnormalities in primary APS evolving into SLE: 6 years follow-up in women with repeated pregnancy loss

Abstract: We have performed a prospective study to determine the prevalence of immunological abnormalities and the evolution from primary antiphospholipid syndrome (APS) into systemic lupus erythematosus (SLE) in women who had had unexplained repeated pregnancy loss (PL) and APS. Of 105 women with abortions or fetal deaths, 33(31%) fulfilled criteria for APS. Among these patients with primary APS, 24% had antinuclear antibodies (ANA), 91% had elevated circulating immune complexes (CIC), 70% had low total haemolytic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…These findings were recently confirmed in rats by Fischetti et al [10•], who showed that thrombus formation induced by antibodies to 2 -GPI requires a priming factor such as bacterial LPS and is complement dependent [10•]. Interestingly, hypocomplementemia has been found in a significant proportion of patients with primary APS, and it was associated with thrombosis in one study and with livedo reticularis and thrombocytopenia in another publication [40][41][42].…”
Section: Activation Of the Complement Cascade And Aplsupporting
confidence: 51%
“…These findings were recently confirmed in rats by Fischetti et al [10•], who showed that thrombus formation induced by antibodies to 2 -GPI requires a priming factor such as bacterial LPS and is complement dependent [10•]. Interestingly, hypocomplementemia has been found in a significant proportion of patients with primary APS, and it was associated with thrombosis in one study and with livedo reticularis and thrombocytopenia in another publication [40][41][42].…”
Section: Activation Of the Complement Cascade And Aplsupporting
confidence: 51%
“…Likewise, Carbone et al demonstrated that the presence of ANA in 33 women with PAPS represented a greater risk of evolution of PAPS into SLE in six patients. 26 The association found in the present study between ANA Hep-2 positivity and a higher frequency of aCL antibodies cold suggest a polyclonal activation of lymphocytes in APS. This activation has been demonstrated by the presence of at least 30 different types of autoantibodies related to APS.…”
Section: Discussionsupporting
confidence: 56%
“…Others and we have suggested an important role of complement (mainly C1q) and DNaseI in the clearance process of dying cells and subcellular fragments [18][19][20][21][22][23][24][25][26]. Patients with primary antiphospholipid syndrome who have low levels of the complement components C3 and C4 and low CH 100 values also show immunologic alterations similar to those of SLE [27]. The fast and efficient uptake of dying cells is of main importance to prevent contact of the immune system with intracellular autoantigens.…”
Section: Introductionmentioning
confidence: 93%